Small volatile lipophilic molecules induced belowground by aphid attack elicit a defensive response in neighbouring un-infested plants - Cascone, Pasquale; Vuts, Jozsef; Birkett, Michael A.; Rasmann, Sergio; Pickett, John A.; Guerrieri, Emilio (Frontiers in Plant Science, 2023)
In pioneering studies on plant-aphid interactions, we have observed that Vicia faba plants infested by aphids can transmit signals via the rhizosphere that induce aboveground defence in intact, neighbouring plants. The aphid parasitoid Aphidius ervi is significantly attracted towards intact broad bean plants grown in a hydroponic solution previously harbouring Acyrtosiphon pisum-infested plants. To identify the rhizosphere signal(s) possibly mediating this belowground plant-plant communication, root exudates were collected using Solid-Phase Extraction (SPE) from hydroponically grown 10-day old A. pisum-infested and un-infested Vicia faba plants. We identified three small volatile lipophilic molecules as plant defence elicitors: 1-Octen-3-ol, Sulcatone and Sulcatol, in SPE extracts of A. pisum-infested broad bean plants. In wind tunnel assays, we recorded a significant increase in the attractiveness of A. ervi towards V. faba plants grown in hydroponic solution treated with these compounds, compared to plants grown in hydroponics treated with ethanol (control). Both 1-Octen-3-ol and Sulcatol have asymmetrically substituted carbon atoms at positions 3 and 2, respectively. Therefore, both enantiomers for each have been tested alone as well as the complete mixture. We highlighted a synergistic effect on the level of attractiveness towards the parasitoid when testing the three compounds together in respect of the response recorded against each of them. These behavioural responses were supported by the characterization of leaf volatiles released by tested plants. These results shed new light on the mechanisms underlying plant-plant communication belowground and prompt the use of bio-derived semiochemicals for a sustainable protection of agricultural crops.